Characteristics of Independent Commissioners and Company Performance on the Quality of Sustainability Reports: A Literature Review - Pratiwi, Bella Noviani; Evana, Einde; Oktavia, Reni (LPPPIPublishing, 2023)
This study examines the intricate dynamics of sustainability reporting by investigating the influence of independent commissioners, company size, and performance on the quality of sustainability reports. Employing a literature review spanning the last decade and drawing insights from SINTA and Scopus databases, the analysis utilizes financial ratios such as leverage, liquidity, and profitability as key indicators. The results indicate a positive correlation between the number of independent commissioners and the quality of sustainability report disclosures, emphasizing their crucial role in enhancing transparency and oversight. Companies demonstrating a sincere commitment to sustainability, supported by adequate resources and integrated sustainability metrics, exhibit superior report quality. Additionally, larger firms consistently outperform their smaller counterparts, producing more comprehensive and higher-quality sustainability reports. The implications underscore the significance of strategic balance, irrespective of company size, between financial and sustainability considerations for optimal reporting credibility and impact.